The Impact Of Individual Characteristics And Self-Efficacy On Employee Performance - Suki, Priska Henderina; Timuneno, Tarsisius; Riwu, Yonas Ferdinand (STIE AMKOP, 2025)
This study aims to describe Individual Characteristics, Self-Efficacy and Employee performance and analyze the influence of Individual Characteristics and Self-Efficacy in a persuasive and simultaneous manner on Employee performance. The research method used in this study is a descriptive method. The type of research used is quantitative. The sample used in this study is an employee of KOPDIT Serviam Oebufu Branch with a sample of 35 sample respondents in this study. The primary data collection technique uses the questionnaire technique The results of the study show that Individual Characteristics do not have a significant positive effect on Employee Performance, Self-Efficacy has an effect on Employee performance, thus the higher the level of employee discipline at work, the more their performance increases, Individual Characteristics and Self-Efficacy together affect Employee Performance. Keywords: Individual Characteristics, Self-Efficacy, Employee Performance.